Learning spillovers in the firm - Emily Nix (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
To produce output for a firm, coworkers often interact. This paper examines the possibility that as a byproduct of these interactions, there are learning spillovers: coworkers learn general skills from each other that increase future productivity. In the first part of t he paper I show that l earnings pillovers imply externalities in the return to human capital which firms may not internalize when there is asymmetric information. As a result, individuals may inefficiently invest in their own education. Next, I show that learning spillovers are empirically relevant. Using matched administrative data from Sweden and a combination of fixed effects and controls to address bias from worker sorting and firm heterogeneity, I find that increasing the average education of a given worker's coworkers by 10 percentage points increases that worker's wages in the following year by 0.3%, which is significant at the 1% level. The effect is persistent, decreases with age, and is higher for workers in occupations where they interact more regularly with their coworkers.
Keywords: E24; J24; 330; Human Capital Accumulation; Diffusion of Knowledge; Learning